Pityphyllum mercedes-abarcae (Maxillariinae) a new species from Euador - Vélez-Abarca, Leisberth (2021)
A new species of Pityphyllum from south-eastern Ecuador was found during an investigation of the orchids of the Cordillera del Cóndor. Pityphyllum mercedes-abarcae is described and illustrated. Information concerning its distribution, habitat, and phenology is provided. The new proposed taxon is morphologically similar to P. pinoides, from which it differs by the smaller plants, the spathulate petals with an erose margin in the middle third, lip flattened is square in the middle third, wedge in the basal third and acute in the apical third with two small parallel calluses in the apical third, presents a slight cell thickening in the abaxial part of the apical third and elongated trichomes below the stigma.